The Correlation Between Family Functioning and Self-disclosure Among Emerging Adulthood - Muhamad Nanang Suprayogi; Wan Vaynadita (‎‎‎TAZKIYA Journal of Psychology, 2023)
This study aims to examine the correlation between family functioning and self-disclosure among emerging adulthood. Family functioning is a process of physical and emotional interaction between family members in carrying out their duties and striving for the welfare of each member from the physical, social, and psychological aspects. Self-disclosure is the act of providing information about oneself that is usually hidden and not shared with others. This study used a quantitative method involving 111 college student respondents aged 18-25 years who study in West Jakarta and live separately from their parents. Family functioning is measured using the McMaster Model of Family Functioning adapted by Boterhoven de Haan. Meanwhile, self-disclosure is measured using the Self-Disclosure Scale based on the self-disclosure aspects according to DeVito and has been modified to the research context. The research analysis result showed that based on Pearson's correlation analysis, the family functioning has a significant and positive correlation with self-disclosure among emerging adulthood. The better family functioning and better self-disclosure help emerging adulthood in carrying out their academic activities. This study recommends for emerging adulthood to implement good communication patterns and self-disclosure to express themselves, share experiences, and deliver opinions to parents.